FENOMENA ALOE TOGETHER DENGAN PERUBAHAN PERILAKU REMAJA DALAM KELUARGA - Arista Dwi Rahmawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
ABSTRACTAlone together is a condition where a person is more fun using their gadgets than interacting with the surrounding environment. Alone together appears due to several things, namely the duration and time of using the device (HP) in adolescents, applications that are often used by teenagers, the duration and time of communication with family members. The purpose of the study was to determine the phenomenon of alone together with changes in adolescent behavior in the family. This research is a qualitative research using phenomenological research. The informants of this study on students of SMPN 01 Dagangan as many as 6 who experienced alone together out of a total of 10 informants. Data collection is carried out by triangulation of sources, namely parents, teachers and friends of informants. The results of the study conducted on 6 informants obtained statements of experiencing alone together in terms of the duration and time of using the device for more than 5 hours and the time of using the device until late at night, an application that is often used by tik-tok, Youtube and Whatsapp. The duration of the informant's communication with family members is rare and the time of communication during the afternoon and evening (after the maghrib), thus affecting the addiction and emotional, while the other 4 informants do not experience alone together so as not to cause addiction and emotional. The conclusion is that alone together adolescents in the family cause changes in addictive and emotional behavior in their daily lives.